1997
DOI: 10.1143/jjap.36.7404
|View full text |Cite
|
Sign up to set email alerts
|

Descaling Behavior of Type430 Hot-Rolled Stainless Steel Coil

Abstract: Iron oxides can be reduced in a scale by batch annealing treatment in a reducing atmosphere of 7 vol% H2+93 vol% N2 at 1123 K for hot-rolled coils of type430 stainless steel. The heating processes cause cracks, a Cr2O3 layer in the scale and a Cr depleted layer on the substrate. It is possible to produce a large number of cracks in the scale by employing a scale breaker. The ease of descaling is positively related to the amount of bending elongation. Similarly with shot blasting, descaling be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…According to the study of the passivation process, [53,[56][57][58] the reactions of chromium begin with the formation of chromus (Cr 2þ ) species, for example, Cr(OH) 2 . With the increasing potential, Cr 2þ are oxidized into Cr 3þ which subsequently form Cr(OH) 3 . In an acid environment, the chromic hydroxide can convert to chromium oxide expressed by reaction (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of the passivation process, [53,[56][57][58] the reactions of chromium begin with the formation of chromus (Cr 2þ ) species, for example, Cr(OH) 2 . With the increasing potential, Cr 2þ are oxidized into Cr 3þ which subsequently form Cr(OH) 3 . In an acid environment, the chromic hydroxide can convert to chromium oxide expressed by reaction (3).…”
Section: Discussionmentioning
confidence: 99%
“…During the manufacturing process of stainless steel sheets or following the welding of stainless steel components, nitricbased electrolytes are commonly employed as pickling or passivation solutions. [3][4][5][6][7][8] Many studies have confirmed that nitric acid is an efficient passivant to improve the corrosion resistance of stainless steel. And the reason can be summarized into two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The oxide scale on stainless steel, however, has a very fine structure, generally has a greater thickness and is tightly adherent. 14 Therefore, the stainless steel pickling solution should be much more aggressive than those for mild steel. Such solutions contain at least one acid and one oxidant for dissolving the base metal and the Cr-depleted layer.…”
Section: Introductionmentioning
confidence: 99%